1993
DOI: 10.1200/jco.1993.11.5.850
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin and vincristine for recurrent and newly diagnosed low-grade gliomas of childhood.

Abstract: Carboplatin and vincristine have activity in children with recurrent and newly diagnosed progressive LGGs. Objective responses to treatment after chemotherapy can be seen. This drug regimen is relatively well tolerated, and further studies are indicated to define the role of this combination of drugs in children with newly diagnosed LGGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
203
2
4

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(210 citation statements)
references
References 14 publications
1
203
2
4
Order By: Relevance
“…In a recent update of a study of 29 patients who were treated with the actinomycin-D-vincristine combination and who could be fully evaluated, 12 remained free of subsequent recurrence and radiation therapy was delayed a median of 51 months with more than 70% of patients not requiring radiation therapy until they were at least 5 years old. [11,17] A five-drug regimen consisting of procarbazine, 6-thioguanine, dibromodulcitol, lomustine, and vincristine was used in 42 children with newly diagnosed symptomatic or previously diagnosed progressive low-grade gliomas by a group at the University of California at San Francisco (R Prados, personal communication, 1996). [20] In this series the mean age of the patients was 5 years and the children had a variety of histological types of low-grade gliomas, similar to those treated in the carboplatin and vincristine series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent update of a study of 29 patients who were treated with the actinomycin-D-vincristine combination and who could be fully evaluated, 12 remained free of subsequent recurrence and radiation therapy was delayed a median of 51 months with more than 70% of patients not requiring radiation therapy until they were at least 5 years old. [11,17] A five-drug regimen consisting of procarbazine, 6-thioguanine, dibromodulcitol, lomustine, and vincristine was used in 42 children with newly diagnosed symptomatic or previously diagnosed progressive low-grade gliomas by a group at the University of California at San Francisco (R Prados, personal communication, 1996). [20] In this series the mean age of the patients was 5 years and the children had a variety of histological types of low-grade gliomas, similar to those treated in the carboplatin and vincristine series.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of drugs have been used, including vincristine, actinomycin D, etoposide, carmustine, and carboplatin, as well as combination regimens consisting of these drugs (R. Prados, personal communication, 1996). [5,14,17,18,20,21,24] In 1989, a study was begun to evaluate the efficacy of combining carboplatin and vincristine in treating children with recurrent and newly diagnosed astrocytomas. The objective response rates of 60 children, including 37 with newly diagnosed astrocytomas, have been reported.…”
mentioning
confidence: 99%
“…These pilot trials reported regression or stability of tumors in 75-90% of patients. [82][83][84] At follow-up, children treated on the carboplatin/vincristine regimen before age 5 years, had a 75% 4-year PFS rate. 85 The outcome of a recently-closed COG phase III randomized trial comparing the latter two of these regimens is pending.…”
Section: Gliomas/astrocytomasmentioning
confidence: 99%
“…Carboplatin, cisplatin, vincristine, vinblastine, actinomycin D, lomustine, thioguanine, procarbazine, dibromodulcitol, etoposide, tamoxifen, and temozolomide, alone or in combination, as primary treatment or as adjuvant, have all been utilized. [10][11][12][13]19,[32][33][34][35][36][37][38][39][40] Although chemotherapy has emerged as promising therapy, no regimen has yet to be universally accepted, hence the current Children's Oncology Group trial.…”
Section: Treatmentmentioning
confidence: 99%